The applicability analysis of performance measurement system for small and medium enterprises in Malaysia - Nor Filianie, Aziz (2016)
The Performance Measurement Systems (PMSs) seen as part of a factor that indicates the successful and un-successful company; especially in the Small and Medium Enterprises (SME's) compared with a large company. PMS is an important tool to develop and maintain the company orientation. The roles of PMSs in the SME's business are continuously and responsiveness to achieve the goals. However SMEs management is not as easy as expected and SMEs can fail and bankrupt easily. Meanwhile, PMSs have the potential to predict failure and used as a guide for the survival of companies in the SME sector. The limitations both of SMEs and PMSs makes researcher interested to conduct this study; with three research objectives was developed. The main objective is to determine most preferred PMSs for Malaysian SMEs based on applicability; thus the study was carried out to identify main existing PMSs and to determine the most applicable criteria of PMSs for SMEs. In the methodology, the researcher was used quantitative research design. Whereas quantitative design had been applied with the Analytic Hierarchy Process (AHP) as method analysis. As pointed, experts panel were selected from practitioners and academicians linked with PMSs and SME's in Malaysia. The result and findings show the Balanced Scorecard (BSC) as first ranked of PMS in SMEs. The relevant and suitable PMS model has been future significance guide for Malaysian SMEs development. At the end of the study, the researcher makes the discussion and conclusion; it is also shared the limitation and recommendation to improve and implement the great suitable model in the Malaysian SME's then to academics in future.